Subject-Verb Agreement: A Case Study of BS English Students - Jabeen, Zoya; Qamar, Javeria; Shabbir, Muhammad (Pakistan Languages and Humanities Review, 2024)
This study is aimed to examine the types of written subject verb agreement mistakes made by the students enrolled in BS English program. Second purpose of this study was to check mastering subject verb concord depends whether on language exposure or grip on language. There has been profound research on the reasons of mistakes made by students in subject verb agreement but none has touched upon what sort of mistakes students make mostly, particularly in University of kotli.A study at the University of Kotli has been conducted to examine the subject-verb agreement errors made by students in the BS 5th and BS 1st semesters. Researchers utilized essay writing as their research tool and adopted a qualitative research method. The study's findings indicate that the majority of errors, particularly omissions, were made by BS English 5th semester students. The proportion of students making omission errors is higher than those making misinformation errors, with addition errors being the least common. The results indicate that 5th semester students still struggle with subject-verb agreement, making more errors than 1st semester BS English students despite having more language exposure.